2019
DOI: 10.1111/gere.12315
|View full text |Cite
|
Sign up to set email alerts
|

Refugees in the IT Sector: Young Syrians’ Economic Subjectivities and Familial Lives in Jordan

Abstract: This article explores refugee economic subjectivity in the context of restrictive asylum policies and disrupted transnational family lives. Drawing on fieldwork with young Syrian refugees pursuing IT training in Jordan, I focus on the “coding boot camp,” an emerging educational format in the field of refugee professional training. I thus explore how Syrian youths approach humanitarian policies in which, in the absence of full social and economic rights for refugees, the question of livelihoods is addressed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…6 In these studies, the work permit process is found to be complex and time-consuming, with many employers continuing to employ refugees without permits. 7 My findings expand upon this research into the impact of economic policies on migrants' and refugees' subjectivities 8 and Syrian refugee policies focused on employment in particular. 9 This scholarship offers a critical picture of the merging of humanitarian and economic agendas, looking at the effects of a major policy trend that intersects neoliberal values and refugee policies.…”
mentioning
confidence: 67%
“…6 In these studies, the work permit process is found to be complex and time-consuming, with many employers continuing to employ refugees without permits. 7 My findings expand upon this research into the impact of economic policies on migrants' and refugees' subjectivities 8 and Syrian refugee policies focused on employment in particular. 9 This scholarship offers a critical picture of the merging of humanitarian and economic agendas, looking at the effects of a major policy trend that intersects neoliberal values and refugee policies.…”
mentioning
confidence: 67%
“…In the absence of full social and economic rights for refugees, the problem of livelihoods has in some cases been addressed through assumptions of self-reliance, creativity and innovation, such as coding boot camps for refugees (Pascucci 2019). These have limitations; for example, coding requires education and language skills that not all beneficiaries possess (Schuettler and Caron 2020).…”
Section: Livelihoods and Transformationmentioning
confidence: 99%
“…The study also highlights the complexities of the legal, social and financial conditions these entrepreneurs attempted to mitigate to start businesses. Pascucci (2018), who introduces the concept of economic subjectivity in refugee entrepreneurship, examines young Syrian refugees in the information technology sector who viewed entrepreneurship as an empowerment mechanism to transform their lives from dependent to independent and productive.…”
Section: Syrian Refugees In Jordanmentioning
confidence: 99%